INKLUSI KEUANGAN DAN PROFITABILITAS BANK DI INDONESIA - Novita Widyaningsih; Hersugondo Hersugondo (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
This study was conducted to examine the effect of financial inclusion and bank profitability. The data test method is done manually, which is obtained from the Bloomberg database and the annual reports of banks listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period with a total sample of 17 banks. The data from this study are included in the type of panel data and the data processing technique used is in the form of Least Square Analysis (OLS) using SPSS version 23. The results show that the amount of loans and the number of automated teller machines (ATMs) have a negative and significant effect on bank profitability. meanwhile, the number of bank branches has a positive and significant impact on the profitability of banks in Indonesia.